Living Hadis Inklusif dalam Perspektif Kyai Telingsing, Syekh Ja'far Shodiq dan Raden Umar Sa'id di Kudus (RIWAYAH, 2016)
Undeniably lately potential conflict between elements of Indonesian society increasingly worrying, between the organizations with another organizations of a conflict, between one party with another party blaspheme each other, between one expert to another expert is blame. This condition is exacerbated by widespread behavior spreading false news (Hoak) through in social media, so the president had to intervene to dampen this unnatural behavior. Even more sad again, this does not only happen in Indonesia, but has become a global phenomenon.Hoak outbreak of course can not be separated from the lost of mutual respect and respecting others and far from harmonious and inclusive behavior in the midst of the peoples of Indonesia. Whereas previously the nation Indonesia is known as a nation that good at keeping the feelings of others, respecting others, behave in a harmonious and inclusive and forgiving against others. This condition is realized thanks to the philosophy of its predecessor which is still held firmly, like a life philosophy of Kyai Telingsing, Sheikh Ja'far Shodiq and Raden Umar Sa'id in Kudus.But today it is the philosophy of living in harmony and inclusive inherited by the sunan narrowly missing eroded by the culture of individualism, selfishness and behavior to be selfish so it is not uncommon that emerges is precisely the behavior that led to the division and conflict. Therefore, efforts to revitalize the living tradition of inclusiveness in Kyais Telingsing, Sheikh Ja'far Shodiq and Raden Umar Sa'id in Kudus becomes very important. With hope these efforts can minimize the potential for conflict in the midst of society. This is the main purpose of this article writes//